2008
DOI: 10.1016/j.cub.2008.04.073
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of HIV-1 Isolates that Use a Novel Vif-Independent Mechanism to Resist Restriction by Human APOBEC3G

Abstract: The human APOBEC3G protein restricts the replication of Vif-deficient HIV-1 by deaminating nascent viral cDNA cytosines to uracils, leading to viral genomic strand G-to-A hypermutations. However, the HIV-1 Vif protein triggers APOBEC3G degradation, which helps to explain why this innate defense does not protect patients. The APOBEC3G-Vif interaction is a promising therapeutic target, but the benefit of the enabling of HIV-1 restriction in patients is unlikely to be known until Vif antagonists are developed. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
114
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 30 publications
7
114
2
Order By: Relevance
“…In addition, the persistence of the partially defective vif over 5 years of infection suggests that there was no significant selective pressure against it. Similar to our results, a recent study demonstrated that vif-deficient viruses, which had acquired compensatory mutations, were able to replicate despite extensive G-to-A changes (11).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the persistence of the partially defective vif over 5 years of infection suggests that there was no significant selective pressure against it. Similar to our results, a recent study demonstrated that vif-deficient viruses, which had acquired compensatory mutations, were able to replicate despite extensive G-to-A changes (11).…”
Section: Discussionsupporting
confidence: 92%
“…HIV may take advantage of 63 K-linked poly-Ub A3H, which can associate with Gag through an RNA intermediate or directly (75), to promote virus release. This may aid in virus budding and titrate out the effect of the A3H during viral adaptation akin to how Vif mutants unable to degrade A3G can acquire mutations that enable the production of more virus particles to minimize A3G packaging (76,77). This may occur for A3H since it binds Alu RNA with an apparent K d that is 3-fold higher than A3G (A3H K d of 717 Ϯ 29 nM; A3G K d of 246 Ϯ 46 nM [data not shown]).…”
Section: Discussionmentioning
confidence: 99%
“…These studies yielded viral variants that could spread effectively in the presence of A3G despite retention of these tandem stop codons; rather, all isolates had acquired a pyrimidine at nucleotide 200 and a stop codon in vpr (18). While the effect of the vpr null mutation remains unknown, the substitution of A to T or C at nucleotide 200 (T/C200) functions to optimize viral translation, resulting in increased particle production and a relative decrease in A3G encapsidation to levels tolerable to the viral population (17).…”
mentioning
confidence: 99%